Analysis of parameters influencing the assessment of gait and fall risk in elderly patients with and without a history of falls - Coutinho, António (2012)
Objectives: The aim of this study was to compare parameters that may influence gait (strength, balance, fear of falling, Root Mean Square on the maximal voluntary contraction, Foot Minimum Clearance, stride length, speed and leg support time) and check whether a relationship exists between these parameters and the risk of falling. Materials and Methods: The sample comprised a total of 30 patients who fulfilled the inclusion and exclusion criteria. These were divided by the group with no history of falls (n=15) and the group with a history of falls (n=15). The strength evaluation was performed using the Biodex Isokinetic Dynamometer System; balance using the Berg Scale, the fear of falling through Falls Eficacy Scale, and the Root Mean Square on the maximum voluntary contraction using the surface electromyography, the Foot Minimum Clearance, and stride length, speed and leg support time were assessed by kinematic analysis. To assess the risk of falling was applied Timed Up and Go Test, Performance Oriented Mobility Assessement and Berg Balance Scale. Results: Significant differences in relation to an equilibrium with p=0.000 and the Performance Oriented Mobility Assessement with p=0.001. The remaining parameters were not found statistically significant differences between groups (p>0.05). Conclusion: We conclude that for the group with a history of falls strength, balance and Foot Minimum Clearance and support time left is smaller and the fear of falling, Root Mean Square on the maximal voluntary contraction, velocity and time to support law is superior compared to group with no history of falls.